Comparative study on the annual performance of three types of building integrated photovoltaic (BIPV) Trombe wall system. (15th May 2017) - Hu, Zhongting; He, Wei; Ji, Jie; Hu, Dengyun; Lv, Song; Chen, Hongbing; Shen, Zhihe
Highlights: Comparative study on annual performance of three types of Trombe wall systems. Optimum blind angles over three seasons and time of day are obtained. Total electricity saving of Trombe wall with PV blind is over 45% higher compared to existing PV Trombe walls. Carbon emissions reduction of Trombe wall with PV blind are about 1.5 times that of existing PV Trombe walls. Abstract: Building-integrated photovoltaic (BIPV) Trombe wall system can provide heating/cooling and generate electricity simultaneously. Precedent studies on the BIPV Trombe wall system were focused on two major types, one with PV cells attached to glass (BIPVGTW) and the other with that attached to mass wall (BIPVMTW), characterized by low thermal (BIPVGTW) and electric efficiency (BIPVMTW). This study presents a PV blind-integrated Trombe wall system (BIPVBTW). Adopting developed models on the BIPVBTW, the optimum PV blind slat angles over three seasons (summer, winter and mid-term seasons) and time of day (9:00–17:00) are investigated. Comparative assessment of the three BIPV Trombe wall systems are conducted all year round under Hefei weather conditions, in terms of thermal and electrical performance. The results have illustrated that annual electricity output of BIPVBTW system is similar to that of BIPVGTW system, which is 1.2 times that of the BIPVMTW system. The BIPVGTW system is superior to the BIPVBTW/BIPVMTW systems in cooling load reduction, while using PVBTW/PVMTW heating load is decreased significantly compared to using the PVGTW. Combining electricity generation and cooling/heating load reduction, the total electricity saving of BIPVBTW system is over 45% higher compared to BIPVGTW/BIPVMTW systems. CO2 emissions reduction of the BIPVBTW system are about 1.5 times that of BIPVGTW/BIPVMTW systems.